Concrete crack self-repairing material synergistically mineralized by microorganisms, preparation and application

By using a composite porous carrier loaded with alkalophilic Bacillus and layered double hydroxides in concrete, the problems of microbial survival and long repair cycles were solved, achieving efficient crack self-repair and improved structural durability.

CN121426464APending Publication Date: 2026-01-30YELLOW RIVER INST OF HYDRAULIC RES YELLOW RIVER CONSERVANCY COMMISSION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511713642.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-21
Publication Date
2026-01-30

AI Technical Summary

Technical Problem

Existing microbial mineralization deposition technology faces challenges in microbial survival and long repair cycles in concrete, leading to the death of a large number of microorganisms and the infiltration of environmentally corrosive ions, which threaten structural safety.

Method used

A composite porous carrier loaded with a microbial synergistic mineralizer and layered double hydroxides were used. Alkalophilic Bacillus was loaded onto the composite porous carrier composed of diatomaceous earth and silt of a specific particle size. The layered double hydroxides adsorbed corrosive ions and provided a local pH buffering effect, promoting microbial activity and calcium carbonate deposition.

Benefits of technology

It significantly improves the survival rate and repair efficiency of microorganisms, shortens the repair cycle, forms a dense calcium carbonate barrier to resist external erosion, inhibits steel corrosion, and enhances the impermeability and long-term durability of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121426464A_ABST
    Figure CN121426464A_ABST
Patent Text Reader

Abstract

The invention discloses a microorganism synergistic mineralization concrete crack self-repairing material as well as preparation and application thereof. The self-repairing material comprises a composite porous carrier loaded with a microorganism synergistic mineralizing agent and layered double hydroxides, the composite porous carrier comprises diatomite, silt with the particle size of 100-200 [mu] m and nutrient substances; the microorganism synergistic mineralizing agent comprises bacillus alcalophilus with mineralizing ability; the layered double hydroxide is a MgAl-C3H5O3 <-> type layered double hydroxide or a ZnAl-C3H5O3 <-> type layered double hydroxide; during application, the concrete crack self-repairing material is uniformly mixed with other components of concrete according to the proportion. The calcium carbonate sediment generated by microorganism mineralization seals cracks to form a physical barrier for preventing seawater corrosion, and the layered double hydroxide fixes corrosive ions, inhibits steel bar corrosion and forms a chemical barrier for enhancing structural durability.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a concrete crack self-repairing material, in particular to a microbial synergistic mineralization concrete crack self-repairing material, preparation and application. BACKGROUND

[0002] Based on the crack self-repairing technology of aerobic microbial mineralization deposition, because of its self-triggering, environmental protection, multiple repair and excellent effect, it has become an important research direction to improve the durability of concrete. Compared with the traditional method, MICP technology has the advantages of reducing manual intervention, repairing product and substrate combination, avoiding the release of harmful substances and the like. However, the practical application of the technology faces key challenges: (1) Microbial survival problem: the high alkaline environment inside the concrete, the reduction of pore caused by cement hydration and the action of mixing machinery can easily lead to the death of a large number of unprotected microorganisms and damage their cell structure. The survival state and mineralization activity of microorganisms directly determine the self-repairing performance.

[0003] (2) Repair cycle and erosion protection: the MICP process usually has a long cycle. During this period, the penetration of environmental erosion ions (such as chloride ions) may cause steel corrosion, threatening the safety of the structure. SUMMARY

[0004] The summary part of the present application is used to introduce the concept in a brief form, which will be described in detail in the specific embodiment part. The summary part of the present application is not intended to identify the key features or essential features of the claimed technical solution, nor is it intended to limit the scope of the claimed technical solution.

[0005] Some embodiments disclosed by the present application propose a microbial synergistic mineralization concrete crack self-repairing material, preparation and application to solve one or more of the technical problems mentioned in the background part.

[0006] In the first aspect, some embodiments disclosed by the present application provide a microbial synergistic mineralization concrete crack self-repairing material, which comprises: A composite porous carrier loaded with a microbial synergistic mineralization agent and a layered double hydroxide; The composite porous carrier comprises diatomite, silt with a particle size of 100-200 μm and nutrient substances; The microbial synergistic mineralization agent comprises alkaliphilic Bacillus with mineralization ability; The layered double hydroxide is MgAl-LDHs-C3H5O3 - or ZnAl-LDHs-C3H5O3 - type layered double hydroxide.

[0007] Optionally, the mass ratio of diatomite and silt with a particle size of 100-200 microns in the composite porous carrier is 3:1.

[0008] Optionally, the nutrients include yeast extract, calcium lactate, glucose, urea, beef extract, and peptone, and the mass ratio of each substance is 2-5:1:1-5:2-5:4.5-7.2:7.5-10.

[0009] Optionally, the preparation process of the composite porous carrier loaded with the microbial synergistic mineralization agent comprises: The selected alkaliphilic Bacillus after alkaline domestication is prepared into a spore suspension, the suspension is sucked into the air pressure barrel by negative pressure to make the bacteria enter the pore channels of the composite carrier, and then the dried microbial carrier is placed in an oven at 40 DEG C to dry to constant weight, the surface of the dried microbial carrier is first sprayed with a nutrient layer and then sprayed with a protective layer, and finally placed in an oven at 40 DEG C to dry to constant weight, thereby obtaining the composite porous carrier loaded with the microbial synergistic mineralization agent.

[0010] Optionally, the preparation process of the selected alkaliphilic Bacillus after alkaline domestication comprises: Different alkalinity culture mediums with pH values of 8, 9, 10, 11, 12, and 13 are configured, the Bacillus liquid is cultured in the culture medium with pH=8, the microscope is used to observe the Bacillus in the culture medium, and the bacillus with uniform morphology and fullness is selected according to the morphological characteristics and inoculated into the culture medium with the next alkalinity for culture, the above culture process is repeated, the alkalinity of the culture medium is gradually increased, and finally the alkaliphilic Bacillus capable of stably growing in the high alkaline environment with pH=12 is screened out.

[0011] Optionally, the protective layer is mixed by metakaolin, sodium silicate, and water according to a mass ratio of 1:1.

[0012] In the second aspect, some embodiments of the present application provide an application of the microbial synergistic mineralization concrete crack self-repairing material, wherein 9%-11% of the composite porous carrier loaded with the microbial synergistic mineralization agent and 2%-4% of the layered double hydroxide are added into the concrete.

[0013] Optionally, in the concrete, the layered double hydroxide adsorbs corrosive ions, releases organic anions to provide nutrients for the microorganisms, provides a local pH buffering effect to create an alkaline environment suitable for microbial activity, and accelerates the microbial-induced calcium carbonate deposition process.

[0014] The above-mentioned various embodiments of the present application have the following beneficial effects: the composite porous carrier composed of silt and diatomite with specific particle sizes is adopted, the microorganisms are loaded in the nanoscale ordered multistage pores of the diatomite, the surface of the silt is rough and porous, and the silt is easy to adhere to the pore openings of the diatomite, thereby effectively preventing the microorganisms from escaping from the open pores; The layered double hydroxide material utilizes its ion exchange properties to adsorb corrosive substances such as chloride ions. The lactate and other organic anions released by the layered double hydroxide material provide a continuous nutrient supply for the microorganisms in the loaded composite porous carrier. The local pH buffering effect provided by the layered double hydroxide creates and maintains an alkaline environment more suitable for microbial activity, which significantly promotes the microbial-induced calcium carbonate deposition process. When applied to concrete systems, the calcium carbonate deposits generated by microbial mineralization seal cracks, forming a physical barrier against seawater erosion. The layered double hydroxides fix corrosive ions, inhibit steel corrosion, and form a chemical barrier that enhances structural durability. Attached Figure Description

[0015] Figure 1 Scanning electron microscope images of the cracks after self-repair following the compressive failure in Example 1 are shown, at magnifications of 50x, 500x, and 2000x, respectively. Figure 2 The XRD diffraction pattern of the crack self-healing product of Example 1 is shown below. Figure 3 The crack test block in the example and comparative examples shows the state after 90 days of self-healing. Detailed Implementation

[0016] The present invention will be further described below with reference to the accompanying drawings and specific examples.

[0017] This invention is the first to apply alkaliphilic Bacillus and LDHs in combination to a concrete system. LDHs not only efficiently adsorb harmful corrosive substances such as chloride ions through ion exchange, but also release organic anions such as lactate. These organic anions can be decomposed and utilized by microorganisms, providing a stable source of "nutrients" for maintaining microbial activity in the long term. Crucially, the unique local pH buffering capacity of LDHs creates a more optimized alkaline microenvironment for the MICP process, significantly accelerating the formation rate of calcium carbonate precipitation and drastically shortening the self-healing cycle of concrete. A dual intelligent synergistic protection mechanism is established: on the one hand, microorganisms utilize the nutrients released by LDHs to drive mineralization, generating dense calcium carbonate precipitates that effectively seal cracks and form a physical barrier against external erosion (such as seawater); on the other hand, LDHs continuously fix corrosive ions, significantly inhibiting steel corrosion and constructing a chemical barrier that enhances structural durability. Self-healing particles are prepared using Yellow River sediment-porous carrier composite technology, achieving efficient microbial loading and long-term protection. By combining a "sugar coating layer-protective layer" double-layer spraying granulation process to immobilize bacteria and nutrients, the survival period of microbial spores extends throughout the long-term lifespan of the concrete, ensuring excellent self-healing capabilities even for late-stage cracks. This synergistic system significantly improves the impermeability and long-term durability of concrete.

[0018] The preparation of a self-healing concrete crack material with microbial synergistic mineralization includes the following steps: (1) Microbial alkali tolerance acclimatization: Microbial scale-up culture: Alkalophilic Bacillus was selected and cultured as a single strain in liquid medium. The microbial culture solution, after 24 hours of incubation, was inoculated into the liquid medium at a 1:100 ratio. The culture was incubated at 30℃ with constant temperature and shaking at 130 rpm. The OD value was measured every 2 hours using a UV spectrophotometer. 600 To determine the bacterial culture's activity value and activity value, the bacterial culture is stored at low temperature and periodically activated to maintain its activity. 2) Preparation of culture media with different alkalinity gradients: A liquid culture medium containing 3g meat extract, 10g peptone, 5g sodium chloride, 15g agar powder, and 1L deionized water was used. The pH of the culture medium was adjusted to six alkalinity gradients (8, 9, 10, 11, 12, and 13) using 2mol / L Ca(OH)₂ solution. To achieve stable application of Bacillus in a highly alkaline environment at pH=12, an adaptive evolutionary domestication method with progressively increasing alkalinity was adopted. During the domestication process, a medium at pH=13 was introduced as a key high-intensity stress condition. This step effectively screened out core strains with deep alkali-tolerant mutations, thus ensuring that the finally obtained Bacillus had a high survival rate and stable growth characteristics and excellent performance under the target pH=12 condition. 3) Screening and acclimatization of microorganisms: The expanded bacterial culture was first placed in a culture medium plate at pH 8 and incubated at 30°C for 36 hours. Then, the microorganisms in the culture medium were observed under a microscope. Based on morphological characteristics, if acclimatization was successful, uniform, plump rod-shaped bacteria were observed in the high-alkaline medium, and a large number of bacteria were in the dividing state (in pairs or short chains), while almost no oval dormant spores were visible. This indicates that the bacterial community has adapted to the alkaline environment and is undergoing vigorous vegetative growth, rather than entering dormancy. The bacteria were then inoculated onto plates with the next alkalinity gradient. The selected alkali-resistant Bacillus pasteurellis was placed in culture media with different alkalinity gradients for expanded culture. The above steps were repeated until the OD was measured. 600 The alkalinity was stabilized, resulting in acclimatized microorganisms highly adapted to the concrete environment. The inoculation-culturing-sampling process was repeated, gradually and systematically increasing the alkalinity of the culture environment to obtain target microorganisms that could grow stably in a highly alkaline environment at pH 12.

[0019] (2) Preparation of microbial self-healing agents: 1) Microbial immobilization: The microbial carrier, which is a uniform mixture of diatomaceous earth and Yellow River sediment in a 3:1 ratio, is placed in an oven at 40°C and dried to constant weight. It is then placed in a pressure tank, and the air pump is turned on to remove the air from the tank. The prepared spore suspension is then drawn into the pressure tank under negative pressure and mixed with the carrier. The carrier is immobilized for a certain period of time. Finally, the valve is opened to restore the air pressure inside the tank to the outside atmospheric pressure, and the carrier immobilized with microorganisms is removed. 2) Place the carrier containing microorganisms in an oven at 40°C and dry it to constant weight; 3) Spraying the sugar coating solution: Place the dried microbial carrier in the spray box; mix 40g yeast extract, 40g calcium lactate, 80g glucose, 20g urea, 80g glucose and 1L water to prepare the sugar coating solution, then pour the sugar coating solution into the building paint spray gun, turn on the air compressor and spray the sugar coating solution evenly onto the surface of the microbial carrier.

[0020] 4) Place the microbial carriers coated with sugar coating into an oven at 40°C and dry them to constant weight.

[0021] 5) Spraying protective layer solution: Place the dried microbial carrier in the spray box, mix metakaolin and sodium silicate in a mass ratio of 1:1, and add an equal mass of water to prepare the protective layer solution. Spray the protective layer solution onto the surface of the microbial carrier.

[0022] The microbial carrier with the protective layer was dried in an oven at 40°C until constant weight, resulting in a composite porous carrier loaded with a microbial synergistic mineralizing agent.

[0023] The application method of microbial synergistic mineralization self-healing materials for concrete cracks is as follows: 1250 parts coarse aggregate, 550 parts fine aggregate, 390 parts ordinary Portland cement (PO 42.5), 2 parts polycarboxylate superplasticizer, 5 parts LDHs, 195 parts mixing water, 245 parts microbial self-healing agent, and the LDHs are MgAl-LDHs-C3H5O3. - Layered double hydroxides were prepared by weighing the materials according to the designed mix proportions. LDHs, cement, sand, and crushed stone were placed in a mixer and mixed for 1 minute. A polycarboxylate-based high-performance water-reducing agent and 3 / 4 of the mixing water were mixed evenly and then poured into the mixer and mixed for 90 seconds. Microbial self-healing agent and 1 / 4 of the water were added to the mixer and mixed for another 1 minute. The mixed concrete was poured out and its slump was measured to determine its workability. The mixture was placed into molds of appropriate size and vibrated on a vibrating table. After molding, the molds were gently tapped with a vibrator until slurry appeared on the concrete surface. The mixture was left at room temperature for 24 hours until it was fully formed, after which the molds were removed. The prepared specimens were cured under standard curing conditions for 28 days (curing temperature 20℃±2℃, curing humidity 90±5%) to obtain the prepared microbial self-healing concrete.

[0024] Self-healing concrete was prepared using the microbial self-healing concrete preparation method described in the above embodiments, and the 28-day compressive strength was ≥45MPa. Through verification of the self-healing effect of concrete cracks, after each specimen cracked at 7 days of age and was cured for 28 days, the concrete cracks with added microbial repair agent produced a significant amount of white substance filling the cracks. When the crack width was ≤0.3mm, the self-healing rate within 7 days was >90%; the chloride ion adsorption rate increased by 40%, and the steel reinforcement corrosion current density decreased by 60%.

[0025] Scanning electron microscopy (SEM) was performed on the cracks in the self-healing test blocks prepared using the self-healing concrete described in the above embodiments. The magnifications were 50x, 500x, and 2000x, respectively. The results are as follows: Figure 1 Scanning electron microscopy (SEM) images revealed that a large number of blocky and spherical calcium carbonate particles were generated within the cracks of the self-healing specimens. At 50x magnification, a dense calcium carbonate structure with no obvious gaps was observed; at 500x and 2000x magnification, the calcium carbonate in the repaired cracks maintained good density throughout.

[0026] To investigate the phase composition of the self-healing crack product, powder samples were scraped from the repair site and subjected to X-ray diffraction (XRD) analysis. The obtained diffraction data were processed using MDI Jade 6.0 software to obtain the following results: Figure 2 The diffraction pattern shows typical diffraction characteristics of calcium carbonate. Calcium carbonate mainly exists in the form of calcite, which is the most stable crystal form of calcium carbonate at room temperature and pressure, exhibiting high thermal and chemical stability. This indicates that the calcium carbonate produced possesses good structural stability and can effectively resist changes in the external environment.

[0027] To verify the comprehensive repair performance of the concrete system using the microbial synergistic mineralization self-healing material for concrete cracks described in this invention, the following comparative tests were conducted: Example 1: A concrete system using the microbial synergistic mineralization self-healing material for concrete cracks described in this invention; Comparative Example 1: Based on Example 1, without the addition of a microbial self-healing agent; Comparative Example 2: The microorganisms used in Example 1 were replaced with strains that had not been acclimated to alkali tolerance; Comparative Example 3: Based on Example 1, the protective layer formulation process was eliminated, and the bacterial cells were directly incorporated into the material; Comparative Example 4: Based on Example 1, without the addition of LDHs (layered bimetallic hydroxides). The above-mentioned specimens were subjected to a 60-day repair performance test, with a focus on evaluating crack healing rate and ultrasonic time recovery rate.

[0028] The test results are as follows: The average acoustic time values ​​of the samples are shown in Table 1. To characterize the mortar repair condition based on the acoustic time values, the ultrasonic acoustic time recovery rate is introduced, and its definition formula (1) is as follows: (1) In the formula, η I The ultrasonic time recovery rate; I s The sound time value of the complete test block; I i The sound time value of the unrepaired test block; I r The values ​​represent the acoustic time of the repaired test block. Due to the presence of the crack, the ultrasonic wave propagation path becomes longer, resulting in an increased acoustic time. I i > I s When the repair is effective, internal defects are reduced and acoustic time is shortened, that is... I r < I i .when I r = I s hour, η I =100%, which indicates that the acoustic time of the repaired test block has recovered to the level of the complete test block, and the repair effect has reached the best state.

[0029] Table 1 Results of Ultrasonic Time Detection

[0030] Table 2 Comparison of repair and testing results after 90 days in Example 1

[0031] Test results show that the synergistic material provided by this invention has the best crack repair performance, with a 90-day crack healing rate of 98% and an ultrasonic recovery rate of 99%. Moreover, the repair product is mainly composed of dense calcite, demonstrating excellent self-healing ability and structural recovery performance.

[0032] In contrast, the performance of each comparative example showed varying degrees of decline: Comparative Example 1 (no microorganisms) showed almost no repair effect, indicating that microorganisms are the fundamental driving force of the repair process; The remediation effect of Comparative Example 2 (the strain that has not been acclimated to alkali tolerance) was significantly weakened, indicating that the environmental adaptability of the strain has a key impact on the remediation performance; Comparative Example 3 (without protective layer process) had a healing rate of only 45% and generated a large amount of loose aragonite, reflecting that the protective layer plays an important role in ensuring the activity of the strain and the quality of the mineralized products. Comparative Example 4 (without LDHs) also showed lower performance than the present invention, indicating that LDHs have a synergistic effect in promoting mineral crystal form optimization and repair efficiency. In summary, the complete technical solution of this invention is significantly superior to other comparative solutions in terms of repair efficiency, structural restoration capability, and mineralized product quality, demonstrating a clear synergistic repair effect and advanced technology. The above description is merely a selection of preferred embodiments and an explanation of the technical principles employed. Those skilled in the art should understand that the scope of the invention involved in the embodiments of this disclosure is not limited to technical solutions formed by specific combinations of the above-described technical features, but should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the above-described inventive concept.

Claims

1. A microbial synergistic mineralized concrete crack self-repairing material, characterized in that, The application relates to a composite porous carrier loaded with a microbial synergistic mineralization agent and a layered double hydroxide. The composite porous carrier comprises diatomite, silt with a particle size of 100-200 mu m and nutrients. The microbial synergistic mineralization agent comprises alkaliphilic bacillus with mineralization capacity. The mass ratio of diatomite to silt with a particle size of 100-200 mu m in the composite porous carrier is 3:

1. said layered double hydroxide is of the type MgAl-LDHs-C3H5O3 - or of the type ZnAl-LDHs-C3H5O3 - layered double hydroxide.

2. The microbial synergistically mineralizing concrete crack self-healing material according to claim 1, characterized in that, The nutrients comprise yeast extract, calcium lactate, glucose, urea, beef extract and peptone, and the mass ratio of the nutrients is 2-5:1:1-5:2-5:4.5-7.2:7.5-10.

3. The microbial synergistically mineralizing concrete crack self-healing material according to claim 1, characterized in that, The alkaliphilic bacillus with mineralization capacity comprises at least one of bacillus pasteurii, bacillus cohnii, bacillus globigii, bacillus cereus, bacillus licheniformis and bacillus subtilis.

4. The microbial synergistically mineralizing concrete crack self-healing material according to claim 1, characterized in that, The preparation process of the composite porous carrier loaded with the microbial synergistic mineralization agent comprises the following steps:

5. The microbial synergistically mineralizing concrete crack self-healing material according to claim 1, characterized in that, The alkaliphilic bacillus selected after alkaline domestication is made into a spore suspension, the suspension is sucked into a gas pressure barrel through negative pressure so that the bacillus enters the pore channel of the composite carrier, then the composite carrier is placed in an oven at 40 DEG C and dried to constant weight, the surface of the dried microbial carrier is first sprayed with a nutrient layer and then sprayed with a protective layer, finally the composite carrier is placed in an oven at 40 DEG C and dried to constant weight, thereby obtaining the composite porous carrier loaded with the microbial synergistic mineralization agent. The preparation process of the alkaliphilic bacillus selected after alkaline domestication comprises the following steps:

6. The microbial synergistically mineralizing concrete crack self-healing material according to claim 5, characterized in that, Culturing media with different alkalinity of pH values of 8, 9, 10, 11, 12 and 13 are configured, the bacillus liquid is cultured in the medium with pH=8, a microscope is used to observe the bacillus in the medium, and bacillus with uniform morphology and fullness is selected according to morphological characteristics and inoculated into a medium with the next alkalinity for culture, the above culture process is repeated, the alkalinity of the medium is gradually increased, and finally the alkaliphilic bacillus capable of stably growing in a high-alkalinity environment with pH=12 is screened out. The protective layer is mixed by mixing metakaolin, sodium silicate and water according to a mass ratio of 1:

1.

7. The microbial synergistically mineralizing concrete crack self-healing material according to claim 5, characterized in that, 9%-11% of the composite porous carrier loaded with the microbial synergistic mineralization agent and 2%-4% of the layered double hydroxide are added into the concrete.

8. Use of a microbial synergistic mineralized concrete crack self-healing material according to claim 7, characterized in that, In the concrete, the layered double hydroxide adsorbs corrosive ions, releases organic anions to provide nutrients for the microorganism, provides a local pH buffering effect to create an alkaline environment suitable for microbial activity and accelerates the microbial-induced calcium carbonate deposition process.

9. Use of a microbial synergistic mineralized concrete crack self-healing material according to claim 8, characterized in that, ​